Pengaruh Kevakuman terhadap Efektivitas Kondensor PLTU Barru Unit 1 - Apollo Apollo; Musrady Mulyadi; Achmad Yoga Issaniyah; Fefrianto Muh Surahman (Jurnal Teknik Mesin Sinergi, 2014)
The condenser is one of the important equipment in a power plant in the process, especially at the power plant system whose function is to condense the exhaust steam turbine extraction into water droplets (condensate water) which is then circulated back to boiler reprocessed into steam. Vacuum condenser is one of the parameters that influence the effectiveness and efficiency of the condenser in particular plants in general. This final report aims to determine the effectiveness of the condenser based on actual data, the optimal gain vacuum value, and comparison between the specifications and the actual effectiveness of the condenser. The method used is collecting data on the load condition of 50%, 75%, and 100% and then perform data analysis.Results will be presented in tables and graphs then making a conclusion. Based on the data and analysis that has been done, it is known condenser effectiveness decreases with an increase in vacuum pressure. Optimum vacuum level is on a scale (80) Kpa - (85) Kpa. From the analysis of the data also can be seen that the effectiveness of the actual data is higher than the effectiveness of the data specification.